ON TERMINOLOGICAL DERIVATION AND THE EVOLUTIONARY DEVELOPMENT OF SECTORAL VOCABULARY: THE LEXICON OF EMBROIDERY, SKULLCAP-MAKING, AND GOLD EMBROIDERY - Bahodirova Gulruh Bahodirovna (Modern American Journals, 2025)
This article covers the process of terminological derivation and its impact on the field lexicon. The article analyzes semantic changes of terminological derivation, diachronic and synchronic formation methods. Examples of terminological derivation are presented in the lexicon of the field, the formation of intermediate terms and their place in the field through the processes of terminologizing and determinologizing in this field are discussed. Complexities in the lexicon of the field and difficulties in their definition are highlighted through the separation of terminological units such as preterms, quasiterms, terminoids and prototerms. Also, processes of rapid creation of new terms and processing of existing terms as a result of globalization and technological development are analyzed.
Keywords: Terminological derivation, determinologization, terminalologization, preterms, quasiterms, terminoids, prototerms.